Role of Alanine, Arginine and Glutamine on Storage Capacity of Abattoir Derived Epididymal Buck Semen at Refrigerated Temperature - Singh, Hari O.; Singh, Bhoopendra; Singh, Jitendra P.; Kumar, Rajesh; Srivastava, Sushant (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The study was conducted on 48 pairs of abattoir-derived testicles from mature bucks, irrespective of breed. The testicles were collected and packed in plastic bags in an icebox at 4°C and immediately transferred to the laboratory. The testicles were randomly divided into six storage groups, i.e., 6, 12, 24, 48, 72, and 96 hours; 8 pairs of testicles in each group and were preserved in the refrigerator at 4°C. After completion of storage time, testes of respective storage groups were cleaned with physiological saline solution, and the fascia, blood vessels, and sheath were removed using BP blade and thumb forceps. Epididymal semen was harvested, split into four aliquots and diluted with Tris Fructose-yolk-glycerol (TFYG) dilutor without and with additives, viz. alanine @ 25 mM, arginine @ 25 mM, or glutamine @ 50 mM. Ten straws from each diluted aliquot were filled, sealed, and placed in cold handling cabinet at 4°C for further 24 hours of storage. The sperm motility, viability and HOS reactivity were evaluated on dilution and again after 24 hours of cold storage of straws using standard procedures. There was a gradual and significant deterioration in sperm quality with increasing storage time of testes from 6 to 96 hours at 4°C. Inclusion of all three amino acid additives in TFYG dilutor, and glutamine in particular, significantly improved sperm motility, viability, and HOS reactivity on dilution and at 24 hours of cold storage following each interval of testicles’ preservation. Therefore, epididymal semen of elite buck testes preserved at 4°C can be utilized for artificial breeding up to 12-24 hours following dilution with TFYG dilutor containing amino acid additives, particularly glutamine @ 50 mM.